Ces1d deficiency protects against high-sucrose diet-induced hepatic triacylglycerol accumulation - Lian, Jihong (2019)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. Triacylglycerol accumulation in the liver is a hallmark of NAFLD. Metabolic studies have confirmed that increased hepatic de novo lipogenesis (DNL) in humans contributes to fat accumulation in the liver and to NAFLD progression. Mice deficient in carboxylesterase (Ces)1d expression are protected from high-fat diet-induced hepatic steatosis. To investigate whether loss of Ces1d can also mitigate steatosis induced by over-activated DNL, WT and Ces1d-deficient mice were fed a lipogenic high-sucrose diet (HSD). We found that Ces1d-deficient mice were protected from HSD-induced hepatic lipid accumulation. Mechanistically, Ces1d deficiency leads to activation of AMP-activated protein kinase and inhibitory phosphorylation of acetyl-CoA carboxylase. Together with our previous demonstration that Ces1d deficiency attenuated high-fat diet-induced steatosis, this study suggests that inhibition of CES1 (the human ortholog of Ces1d) might represent a novel pharmacological target for prevention and treatment of NAFLD.